The Role of IoT and Big Data Analytics in Driving Sustainable Management Transformation - Simona Corina Dobre Gudei; Elena Gurgu (Annals of Dunarea de Jos University. Fascicle I : Economics and Applied Informatics)
In the digital age, emerging technologies such as the Internet of Things (IoT) and Big Data Analytics play a crucial role in driving the transformation of sustainable management. This article explores how these technologies can support organizations in optimizing resource use, reducing waste and improving operational efficiency, helping to achieve sustainability goals. IoT enables real-time monitoring and data collection through sensors and connected devices, providing valuable information about energy consumption, resource utilization and operational performance. Combined with Big Data Analytics, this information is analyzed to identify patterns, anticipate problems and optimize processes. Case studies from sectors such as manufacturing, transport and energy demonstrate the positive impact of implementing these technologies. For example, by using IoT, companies can monitor energy consumption in real time, thereby reducing carbon emissions and associated costs. Big Data Analytics helps to optimize supply chains, improve logistics and maximize the use of renewable resources. However, data security challenges and high initial investments remain important obstacles. The article concludes that the integration of IoT and Big Data Analytics is a critical step for companies looking to transform their sustainability management, offering significant opportunities for innovation and efficiency.